Risk assessment of a formamidine pesticide, Amitraz, focusing on thyroid hormone receptors (TRs) in rainbow trout, Oncorhynchus mykiss - Meriç Turgut, ć°.; Keskin, E. (Cellular and Molecular Biology, 2017)
Amitraz, a formamidine pesticide, and their metabolites have the potential to disrupt endocrine homeostasis in a variety of organisms, nevertheless there is a lack of information concerning such effects and underlying mechanisms in any fish species.To evaluate the potential impacts of Trasil (EC; active constituent 200 g amitraz/L), a commercial product of amitraz, on thyroid hormone (TH) homeostasis of rainbow trout (Oncorhynchus mykiss); mRNA levels of thyroid hormone receptors (TRs), TRÎ± and TRÎ², were determined by RT-PCR soon after sub-lethal administration in a static bio-assay system. The sub-lethal exposure of 0.84 mg/L amitraz resulted in upregulation of both TRÎ±and TRÎ²genes for muscle and liver, respectively in a tissue-manner, though the differences were found statistically insignificant (P>0.05). The present results emerged an endocrine interaction between amitraz based formulation and TH homeostasis, but still needs further detail studies to a better understanding of TH mechanism in teleosts in response to environmental compounds.